18. Dysfunctional properties of single motor units in ALS. Issue 3 (March 2016) - Howells, James; Park, Susanna B.; Burke, David; Kiernan, Matthew C.
Abstract : Background: Abnormalities in the excitability of lower motor neurons in amyotrophic lateral sclerosis have been extensively examined using threshold tracking techniques. Several studies have found evidence for a down-regulation of K +, and an up-regulation of Na + conductances. The results as a whole however have been somewhat mixed. Threshold-tracking studies test the excitability of a fixed fraction of the maximal compound action potential, and for most disease processes this accurately reflects the excitability of all axons of the same modality within a nerve. However, in ALS such a relationship is unreliable. The slow inexorable process of degeneration of individual motor units is likely to change their excitability, with hyperexcitability and reinnervation believed to impact on their viability. In ALS the disease process itself presents the opportunity to study single motor units identifiable in the recruitment curve, and in particular the large units which result from reinnervation of muscle fibres from motor units that have undergone degeneration. Such measurements provide an unequivocal snapshot of the excitability of an individual motor unit. Methods: Measurements of the excitability of single motor units in the intrinsic muscles of the split hand were undertaken in 7 subjects, and mathematical modelling was performed to examine the nature of changes in individual motor units. Results: As expected, the ALS single motor unit recordings were more varied in nature when compared to normal single motor units from a previous study. Significant differences were observed with a greater rheobasic current and lower resting I/V slope, relative refractory period and 'fanned out' threshold electrotonus in the ALS single motor units compared to the normal controls. Conclusions: The excitability of individual motor units in ALS is heterogeneous in nature, with axonal abnormalities correlated with disease progression. The underlying biophysical mechanisms of these abnormal motor units were best modelled by an increase in the Na + /K + -ATPase pump current, and a near halving of slow K + conductances. The relative proportions of changes to the Na + /K + -ATPase pump and slow K + conductances are likely to vary between individual motor units, and with disease progression.